Representasi Toxic Relationship Dalam Film Sobat Ambyar - Aditya, Aditiya Pramana Putra; Farida; maella, Nur’annafi farni syam (Journal Communication Specialist, 2023)
Taken from the background of the problem that lies behind this research. Researchers want to know the location of the toxic relationship in the film "Sobat Ambyar". Because we know that toxic relationships are still rife among teenagers and adults who are in a relationship of the opposite sex in every relationship.The film Sobat Ambyar tries to explain that we still encounter many toxic relationships even on social media, where many people still don't understand their love relationship and want to continue to force their partner's will rather to follow what is silent as depicted in the film so that many still can't understand the meaning in every plot and every scene created by the script maker. The film Sobat Ambyar is also a form of review so that all viewers understand what things cannot be forced by their own will but must be done by both parties.